Exploitation végétale des oasis d’Arabie - Charlène Bouchaud (Revue d'ethnoécologie)
The recent excavations of Madâ’in Sâlih, ancient Hegra, have revealed the existence of a city inhabited from the 4th century BC and occupied during the Nabataean, Roman and Late Antique periods before its abandonment around the beginning of the 7th century AD. In spite of the arid climatic conditions and the sandy soils, the agricultural exploitation is perceptible through time. Wells allow the use of water from the subterranean resources. The analysis of charred and desiccated plant remains highlights the presence of an oasis agrosystem dominated by the date palm (Phoenix dactylifera L.). The study of various archaeological contexts permits to recognise an optimal daily use of this plant that provides animal and human food products, fuel and building materials. Dates are also used in funerary and ritual practices. Besides the date palm, numerous other cultivated plants constitute a rich plant assemblage that does not change through time and provides a lot of food and craft products. Imported fruits and wood underline the importance of the commercial activities during Antiquity and some products of the oasis are likely to have been involved in such networks.